(untitled) (African Journal of Biomedical Research, 2021)
ABSTRACT Objective: To evaluate the oral health-related knowledge and practices of trainee Community Health Officers. Methodology: A cross-sectional descriptive study conducted using total population purposive sampling method with a self-administered questionnaire on 70 community health officer’s trainees at the centre for training community health officers. Result: Sixty-two trainees (response rate of 88.6%) participated made up of year one (45.2%) and year two 54.8%. %). Mean age of 33.5 years (SD=8.65). By gender, females 90.3% were more than males 9.7% while privately sponsored (53.2%) were more than government-sponsored 38.7% A majority had knowledge of Caries (98.4%), Periodontal disease (93.5%) and Oral cancer (96.8%). Year two trainees had more knowledge about periodontal diseases 54.8% compared to year one 38.5% (p<0.05) Most respondents (91.1%) reported dental visit to be important with 87.1% of the opinion that the visit should not be for pain only; 38.7% felt that dental treatment was expensive. More privately sponsored(51.5% ) compared to government-sponsored (20.8%) felt that dental treatment was expensive (p<0.05). only 11.3% had visited the dentist in the past six months with dental experience gum bleeding (8.1%), dental caries (8.1%), and tooth sensitivity (21%). A majority (85.5%) rated their oral health to be good. Conclusion: The study showed that community health officer trainees have a good knowledge of oral diseases with the year two trainees demonstrating a better knowledge of caries, periodontal disease and oral cancer and self-rated oral health. Their role in oral health promotion programs at the Primary Health Care level should be encouraged to reduce the burden of oral health diseases in the community. Keywords: community health officers, knowledge, oral health, practices, Nigeria Short title: Oral health knowledge and practices of trainee community health officers